A Novel Negative Fe-Deficiency-Responsive Element and a TGGCA-Type-Like FeRE Control the Expression of FTR1 in Chlamydomonas reinhardtii. (31st January 2010) - Fei, Xiaowen; Eriksson, Mats; Li, Yajun; Deng, Xiaodong
Abstract : We have reported three Fe-deficiency-responsive elements (FEREs), FOX1, ATX1, and FEA1, all of which are positive regulatory elements in response to iron deficiency in Chlamydomonas reinhardtii . Here we describe FTR1, another iron regulated gene and mutational analysis of its promoter. Our results reveal that the FeREs of FTR1 distinguish itself from other iron response elements by containing both negative and positive regulatory regions. In FTR1, the− 291/− 236 region from the transcriptional start site is necessary and sufficient for Fe-deficiency-inducible expression. This region contains two positive FeREs with a TGGCA-like core sequence: the FtrFeRE1 (ATGCA GGCT) at− 287/− 279 and the FtrFeRE2 (AAGCGATTGCCA GAGCGC) at− 253/− 236. Furthermore, we identified a novel FERE, FtrFeRE3 (AGTAACTGTTAAGCC) localized at− 319/− 292, which negatively influences the expression of FTR1 .